1999
DOI: 10.1542/peds.104.2.e18
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Infants Prenatally Exposed to Cocaine/Crack: Comparison of a Prenatal Care and a No Prenatal Care Sample

Abstract: These results indicate that exposure to cocaine/crack during early pregnancy decreases the intrauterine growth of exposed offspring in women with and without PC. Each of the growth parameters was affected indicating symmetric growth retardation. The adequacy of PC was not a significant factor in determining the difference between cocaine-exposed and nonexposed infants. These samples are being followed throughout childhood to determine whether there are long-term effects of prenatal cocaine/crack exposure on gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 53 publications
4
49
0
1
Order By: Relevance
“…In addition to the association between PCE and temperament that was identified in this study, we have previously reported that first trimester cocaine use was a significant predictor of reduced gestational age [73] and neurobehavioral and neurophysiological changes at birth [72,77]. Brain development during pregnancy is characterized by a complex interaction of genetic, neurochemical, and environmental factors [29].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In addition to the association between PCE and temperament that was identified in this study, we have previously reported that first trimester cocaine use was a significant predictor of reduced gestational age [73] and neurobehavioral and neurophysiological changes at birth [72,77]. Brain development during pregnancy is characterized by a complex interaction of genetic, neurochemical, and environmental factors [29].…”
Section: Discussionsupporting
confidence: 53%
“…Women were enrolled prenatally and interviewed about their drug use at the end of each trimester of pregnancy. At birth, infants who were exposed to cocaine prenatally were smaller and had reduced gestational age compared to those who were not exposed [73]. The exposed infants also had poorer autonomic stability, state regulation, and motor maturity on the Brazelton Neonatal Behavioral Assessment Scale (BNBAS) at birth [72], and less mature brain development on EEG-sleep studies at both birth and 1 year of age [77].…”
Section: Discussionmentioning
confidence: 99%
“…Research on prenatal malnutrition indicates that growth of brain structures, and therefore head size, recover after nutritional rehabilitation [23], providing an explanation for why head circumference in this cohort may have been affected by cocaine at birth but not at 6 years. While lower growth parameters have been found consistently for prenatally cocaine-exposed children when evaluating outcomes at birth [4,5,9,12,31,36], findings for long-term growth outcomes to age 7 are inconclusive [11,30].…”
Section: Discussionmentioning
confidence: 99%
“…Related to fetal growth however, there are consistent findings indicating that after consideration of a large number of covariates, prenatal cocaine exposure has specific effects on infant birth parameters including head circumference, weight and length [4,5,9,11,12,31,37,41]. Growth deficits are believed to result from poor maternal nutrition, restricted placental blood flow or some other unknown mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] The timing and amount of fetal exposure to cocaine, tobacco, and alcohol during pregnancy also have been noted to influence birth weight. 2,10,11,14 Infants born to women who stopped smoking had higher birth weights than did those born to women who reduced smoking or who did not change behavior. 10,11 Infants born to women who drank throughout pregnancy had smaller head sizes than did those born to women who stopped drinking in the second trimester or who did not drink during pregnancy.…”
mentioning
confidence: 99%